ANALISIS KESULITAN MAHASISWA DALAM MENYELESAIKAN SOAL DIFERENSIAL PADA MATA KULIAH MATEMATIKA DASAR - Mishbah Ulhusna; Deby Erdriani; Yulia Retno Sari (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
Its research is a descriptive qualitative research. The sampling method in this study used purposive sampling with 10 Informatics Management students in the first semester of the 2022/2023 academic year as subjects, who took Basic Mathematics courses. These students have difficulty solving differential problems, especially material on chain rules and high-order derivatives. The results of the Mid Semester Examination (UTS) obtained were only able to be answered by 20% of students. The purpose of this study was to analyze students' difficulties in answering differential questions, done by looking at learning outcomes and by collecting information obtained during interviews, based on four aspects of expertise, namely: 1) Information skills, 2) Arithmatics skills, 3) Language skills, and 4) Number fact skills. The method of information analysis is carried out by: collecting information, reducing, presenting information, and drawing conclusions. Data collection in this study used a triangulation procedure, namely by equating the information on the test results with the results of the interviews. The results of this study are that students have difficulty solving differential problems when viewed from the four aspects of expertise. Factors causing difficulties in this ability are 1) students are not able to analyze the correct method that will be used to solve the differential function reduction, 2) students do not understand mathematical operations well, and 3) students make mistakes reading and interpreting questions.